(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2025)
Corporate sustainability reporting by public healthcare institutions is essential not only for addressing environmental and social issues but also for ensuring long-term economic stability. This study analyses the implementation requirements of the Corporate Sustainability Reporting Directive (CSRD) and the European Sustainability Reporting Standards (ESRS) in the healthcare sector, with a particular focus on large hospitals. Furthermore, the study compares the transposition of the CSRD into the national laws of Latvia, France, and Germany, highlighting key differences, such as sanctioning mechanisms. The research employs comparative legal analysis, content analysis, and legal norm interpretation methods. The results indicate that, unlike Latvia, France and Germany have adopted strict penalties for companies and their managers for non-compliance with CSRD requirements to promote accurate and reliable sustainability reporting. The study finds that Latvian healthcare institutions meeting the CSRD criteria, such as Pauls Stradiņš Clinical University Hospital, will be required to establish sustainability reporting systems by 2026. Consequently, the study’s findings are applicable to other CSRD member states when assessing the obligations of various companies or institutions to provide sustainability reports. In addition to challenges, the study emphasizes potential benefits for businesses, including enhanced reputation. These findings also provide valuable insights for policymakers working on the development of effective regulations and the implementation of sustainability reporting in the healthcare sector.